Analisis Peningkatan Omzet dan Profitabilitas pada UMKM Bakso Kuah Di Lapangan Vatulemo Kota Palu - Nuramanda Rizkiyah; Dinda Ayu Sintawati; Lia Natalia Sonda; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The existence of Micro, Small, and Medium Enterprises, particularly the meatball soup business in Vatulemo Field, Palu City, plays a crucial role in strengthening the local economy by providing employment and encouraging community creativity. This study aims to explore the factors influencing the increase in turnover and profitability of the meatball soup Micro, Small, and Medium Enterprises. The method applied is a case study with a qualitative approach, which aims to identify internal and external factors that contribute to business growth. The analysis results show that the characteristics of a product that is in high demand, a strategic location, and effective business management are the main strengths, while limited capital and marketing management remain challenges. Great opportunities arise from high market demand and government support, but the existence of business competition and rising raw material costs are threats that must be considered. With the use of appropriate strategies, Micro, Small, and Medium Enterprises can significantly increase turnover and profitability.